The effects of COVID-19 on Polish enterprises - Kuryłek, Wojciech; Shachmurove, Yochanan (Economics and Business Review, 2025)
The COVID-19 pandemic had massive impacts on economic sectors. This paper explores the economic effects of COVID-19 on 150,000 Polish enterprises. The paper analyses financial data from the Polish National Court Register and explores heterogenous impacts brought by the COVID-19 pandemic across multiple sectors. Its innovative contribution lies in adopting a granular perspective to assess the sector-specific impacts of COVID-19. This approach distinguishes the paper from much of the existing literature, which predominantly emphasises global or macroeconomic outcomes. The paper compares financial ratios across 2019 and 2020, applying Wilcoxon and Mann-Whitney tests to measure changes in profitability, liquidity, working capital, and leverage ratios. Key findings indicate a disparity in revenues across sectors, with some showing resilience in adapting to pandemic-induced challenges. The analysis reveals that 28 PKD divisions experienced significant revenue reductions (up to −70% in tourism-related sectors), while 25 divisions experienced gains (up to +23% in Information Technology sectors).